Case report: Obstructive jaundice caused by biliary cystadenoma - Li, Yun-cheng; Shi, An-da; Li, Kang-shuai (Frontiers in Oncology, 2023)
Biliary cystadenoma (also called mucinous cystic neoplasm with low-grade intraepithelial neoplasia) is a rare cystic tumor which arises from the biliary epithelium. Jaundice is a rare presentation of intrahepatic biliary cystadenoma which can lead to a diagnostic dilemma. Herein, we present a case of intrahepatic biliary cystadenoma primarily exhibited as jaundice. A 56-year-old woman have suffered from yellow staining of skin and sclera for more than 1 month. She had poor appetite and mild epigastric pain. Laboratory examination showed elevated levels of total bilirubin and elevated CA19-9. A contrast-enhanced computed tomography of the abdomen showed a 7.4*5.3cm oval low-density lesion in the left liver parenchyma with clear boundary and visible septa. The common bile duct was obviously dilated with wall thickening. On magnetic resonance imaging, the lesion in liver showed a multilocular cystic, unenhanced long T2 signal. There was local thickening of the common bile duct wall with short T2-like filling defects and high signal intensity on DWI. He was clinically suspected of having either biliary cystadenoma or a malignancy, such that resection was performed. Macroscopically, the excised tissue specimen showed a polypoid mass in the common bile duct, which extended along the bile duct to the intrahepatic bile duct. There was a cystic and solid mass in the left liver with yellow turbidified fluid, which was associated with the polypoid in the common bile duct. Histopathology suggests mucinous cystadenoma of liver and hilar bile duct. The differential diagnosis of biliary cystadenoma and treatment selection has been discussed.